LINGUOPOETIC FEATURES OF AMERICAN AND BRITISH REALISM: A COMPARATIVE STUDY OF CHARLES DICKENS AND MARK TWAIN - Erkinova Aziza (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
This article examines the linguopoetic features of American and British literary realism through a comparative study of two major authors: Charles Dickens and Mark Twain. By analyzing their narrative techniques, stylistic devices, and use of language, the study highlights the similarities and differences in their approaches to realism. Dickens’ works represent the social consciousness and moral concerns of Victorian Britain, while Twain’s writings reflect the humor, vernacular, and socio-cultural realities of 19th-century America. This comparative study aims to provide a deeper understanding of how linguistic and poetic elements shape literary realism in different cultural contexts.